Leveraging Public Transport Route Innovations as Technological Inspiration for Advancing Islamic Education - Stiya Mulyani, Pamungkas; Syam , Robingun Suyud El (Journal of Scientific Insights, 2024)
The problems and challenges that exist in Islamic education, both in learning and its application, are multidimensional, including the decline in children's innovative abilities due to the influence of digital products. This article aims to review unique writing on public transport routes: inspiration for innovation in Islamic education. This paper is set in qualitative library research, with inductive analysis. The results of the discussion show that the unique writing on public transport routes is intentional, the result of innovation from the owners of these vehicles. This fact can be used as inspiration for Islamic education, that innovative processes can be obtained from various sources and then contextualized into the learning process. Research implications for the direction of interdisciplinary research to build Islamic education based on contextual teaching and learning. The research hopes to contribute to Islamic education.